Investigation of electrical treeing in perspex material - Abderrazzaq, Mohammad (Applied Research and Smart Technology (ARSTech), 2021)
Perspex has been known for a long time as a polymeric material, and it has been used for a large number of electrical and non-electrical applications. The present work was carried out to investigates the ageing mechanism of perspex material under a high electric field. The electrical treeing phenomenon was studied using perspex samples with electrodes of a pin-to-plane configuration. The growth of an electrical tree in Perspex was measured and analysed with the aid of an advanced microscope, equipped with a high-resolution camera and connected to a personal computer. Several distinct stages were assigned to characterise the electrical tree development. The area occupied by the electrical tree channels was calculated using equal-area squares. This approach was employed to measure the growth rate of electrical trees under dry and wet conditions. The tree construction, shape and growth speed were studied and analysed to distinguish between treeing phenomenon under wet and dry conditions of fabricated perspex specimens. The absorption of water has increased the tree growth inside the samples, and ions with water have accelerated the breakdown process. The findings of this study are essential to improve the performance of perspex material, which is widely used in a variety of applications for both energy and non-energy purposes.